Fear as a Political Propaganda: A Study on Politics of Fear by Al Gore - Baral, Madan Prasad (Journal of NELTA Gandaki, 2023)
The practice of creating fear for personal interest or the interest of the political party is common throughout the world. Politicians use any sort of practice for power hunting. Fear not only influences the discourse but also shapes knowledge and reasoning capacity thereby creating an illusion in people. To expose illusion, counter-discourse or positive discourse is required. This study aims to explore how counter-discourse exposes illusion and creates awareness taking reference from the text ‘Politics of Fear’ by Al Gore. The study is done using the document analysis method and the information is analysed based on the framework consisting of five discursive strategies viz. framing, countering publicly, and counter-discursive strategies (logical inversion, parody, complexification, partial reframing and radical reframing) for contesting the mainstream discourse as introduced by Macgilchrist (2007). It is argued that ‘Politics of Fear’ by Al Gore was an attempt to create awareness among the public against propaganda created by the then US President George W. Bush during election through the television advertisements.